France and the Boer War: II : the death of Villebois-Mareuil to the end of the war (Historia, 2021)
-
Keywords: Kruger S.P.J.; De Villebois Mareuil G.H.A.M.V. Count; History; Zuid-Afrikaansche Republiek; Anglo-Boer War 1899-1902; France